2019
DOI: 10.1002/anie.201902137
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of a Micelle Payload via Sequential Enzymatic and Bioorthogonal Reactions in Living Systems

Abstract: Abioorthogonal approach is explored to release the content of nanoparticles on demand. Exploiting our recently described click-and-release technology,w ed eveloped an ew generation of cleavable micelles able to disassemble through as equential enzymatic and bioorthogonal activation process. Proof-of-concept experiments showed that this new approach could be successfully used to deliver the substances encapsulated into micelles in living cells as well as in mice by two complementary targeted strategies.Supporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 28 publications
0
53
0
Order By: Relevance
“…The hydrophobic part of the polymer comprises the core of NPs, and the coating of PEG is the outer layer of particles. The researchers have also synthesized the fluorescence-labeled polymers sensitive to light, enzymes, temperatures, pH, ultrasound, or redox to prepare PEGylated NPs to improve drug delivery and bioimaging [36][37][38][39][40][41][42][43] . The different copolymers are selected to prepare NPs with other functions and provide very high surface graft density under self-assembly strategies.…”
Section: Molecular Self-assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrophobic part of the polymer comprises the core of NPs, and the coating of PEG is the outer layer of particles. The researchers have also synthesized the fluorescence-labeled polymers sensitive to light, enzymes, temperatures, pH, ultrasound, or redox to prepare PEGylated NPs to improve drug delivery and bioimaging [36][37][38][39][40][41][42][43] . The different copolymers are selected to prepare NPs with other functions and provide very high surface graft density under self-assembly strategies.…”
Section: Molecular Self-assemblymentioning
confidence: 99%
“…The different copolymers are selected to prepare NPs with other functions and provide very high surface graft density under self-assembly strategies. However, the synthesis of these copolymers is relatively complex and requires precise operation and reasonable condition control 38 . Also, studies have shown that the polymeric NPs prepared by emulsification have higher PEG coverage than those by nanoprecipitation 44,45 .…”
Section: Molecular Self-assemblymentioning
confidence: 99%
“…In recent years, sydnones and imino‐sydnones were identified as promising dipoles for strain‐promoted ligation with cyclooctynes . These transformations hold much promise for click and bioorthogonal chemistry and a variety of applications were reported in living cells and organisms …”
Section: Methodsmentioning
confidence: 99%
“…[108] In 2019, the same group described the generation of cleavable micelles able to disassemble by using click-and-release technology via a sequential enzymatic and bioorthogonal activation process, and the results indicated that the method could be applied to deliver the substances encapsulated into micelles in living cells as well as in mice. [109] They also synthesized the group of substituted iminosydnones and explored the structure-activity relationship between the compounds and strain alkynes (Figure 22). [110] Very recently, Kolodych and Wagner achieved the synthesis of monodisperse antibody-conjugated drugs using the reaction of iminosydnones and ring strain alkynes.…”
Section: Strain-promoted Cycloaddition Leading To Bioorthogonal Cleavmentioning
confidence: 99%